Implementasi Kebijakan Ekonomi Digital di Indonesia: Tinjauan Hukum atas Perlindungan Konsumen dan Tantangan Inovasi Teknologi - Rohmatur Robiatus Saniyah; Akhmad Farroh Hasan (MLIJo: Journal of Law and Islamic Thought, 2026)
Digital transformation has become a major force in shaping the direction of Indonesia's economic growth, but the implementation of digital economy policies still faces various legal and technological challenges. This research aims to examine the implementation of digital economy policies in Indonesia with a focus on consumer protection and technological innovation challenges. The method used is a qualitative approach with descriptive analysis through literature studies that refer to various secondary sources such as scientific journals, laws, articles, and official policy documents. The results of the study show that the Indonesian government has formulated a comprehensive digital economy policy through strengthening digital infrastructure, increasing digital literacy, and drafting regulations. However, legal regulations such as Law No. 8/1999 and ITE Law are considered not fully responsive to the complexity of modern digital transactions, such as personal data protection and online dispute resolution. In addition, infrastructure gaps, low access to technology in remote areas, and limited digital skills of the community are the main obstacles.